Catalysts-Looking Back and Peering Ahead - Hohn, Keith L. (My University, 2017)
I am pleased to report on the latest happenings at Catalysts. It is gratifying to me to look back at where we’ve been and what we’ve accomplished, but also inspiring to peer ahead to how we will grow and improve.
Citation: Hohn, K. L. (2017). Catalysts-Looking Back and Peering Ahead. Catalysts, 7(2), 1. doi:10.3390/catal7020041
Keywords: Chemistry